2013
DOI: 10.1200/jco.2013.31.26_suppl.70
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of triple-negative versus non-triple-negative breast cancers managed with breast-conservative therapy.

Abstract: 70 Background: Triple-negative breast cancer represents a subgroup of breast cancer associated with aggressive behavior and high risk of local and regional failure. Aggressive surgical intervention is considered optimal for this cancer which has made role of Breast conservative therapy (BCT) debatable in these patients. The objective of this study was to compare outcome of BCT for triple negative versus non-triple–negative breast cancers. Methods: Data of patients who underwent breast conservative therapy bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our study, 3-year, 5-year and 10-year OS were 82%, 72% and 64%, respectively. Also, in patients with TNBC in a London population, the 5-year survival was 62% (Pal et al, 2014) and in other research was 78% (Bhatti et al, 2014) and in center of Iran was 90%. (20) These results showed that OS in West Iran (our study) is less than other studies except to London that was very less.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 3-year, 5-year and 10-year OS were 82%, 72% and 64%, respectively. Also, in patients with TNBC in a London population, the 5-year survival was 62% (Pal et al, 2014) and in other research was 78% (Bhatti et al, 2014) and in center of Iran was 90%. (20) These results showed that OS in West Iran (our study) is less than other studies except to London that was very less.…”
Section: Discussionmentioning
confidence: 99%